2013
DOI: 10.1371/journal.pone.0054446
|View full text |Cite
|
Sign up to set email alerts
|

Does Perceptual-Motor Calibration Generalize across Two Different Forms of Locomotion? Investigations of Walking and Wheelchairs

Abstract: The relationship between biomechanical action and perception of self-motion during walking is typically consistent and well-learned but also adaptable. This perceptual-motor coupling can be recalibrated by creating a mismatch between the visual information for self-motion and walking speed. Perceptual-motor recalibration of locomotion has been demonstrated through effects on subsequent walking without vision, showing that learned perceptual-motor coupling influences a dynamic representation of one's spatial po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 40 publications
(55 reference statements)
3
19
0
Order By: Relevance
“…Rieser and colleagues proposed a functional perceptual-motor account of adaptation, supported by the results that the adaptation generalized to other forms of locomotion that served translating through space (e.g., side stepping), but not to nonlocomotor functions such as throwing. However, more recent work questions this claim with results that show stronger recalibration effects linked to a specific mode of locomotion (Kunz, Creem-Regehr, & Thompson, 2013), or conversely, that effects of continuous visual feedback while walking more broadly generalize to changes in perception of environmental scale (Kelly, Donaldson, Sjolund, & Freiberg, 2013). Furthermore, there is also the suggestion that some apparent adaptation effects are due to specific strategies employed or cognitive correction (Mohler, Creem-Regehr, & Thompson, 2006;Richardson & Waller, 2005).…”
Section: The Calibration Of Locomotionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rieser and colleagues proposed a functional perceptual-motor account of adaptation, supported by the results that the adaptation generalized to other forms of locomotion that served translating through space (e.g., side stepping), but not to nonlocomotor functions such as throwing. However, more recent work questions this claim with results that show stronger recalibration effects linked to a specific mode of locomotion (Kunz, Creem-Regehr, & Thompson, 2013), or conversely, that effects of continuous visual feedback while walking more broadly generalize to changes in perception of environmental scale (Kelly, Donaldson, Sjolund, & Freiberg, 2013). Furthermore, there is also the suggestion that some apparent adaptation effects are due to specific strategies employed or cognitive correction (Mohler, Creem-Regehr, & Thompson, 2006;Richardson & Waller, 2005).…”
Section: The Calibration Of Locomotionmentioning
confidence: 99%
“…Interestingly, this same manipulation did not affect verbal reports in real-world judgments, providing support for a spatial updating or functional account of recalibration, revealed only through subsequent action in the real world. Kunz et al (2013) further tested the functional account in a study examining perceptual-motor recalibration with walking and wheelchair locomotion, with normally walking participants. Using an HMD-VE, participants adapted to faster or slower visual motion while either walking or moving in a wheelchair.…”
Section: Effects Of Feedback and Proposed Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a large amount of previous work that focuses on visuomotor recalibration through closed-loop interactions in real world [Rieser et al 1995;Bingham and Pagano 1998] as well as in VE's [Mohler et al 2006;Kunz et al 2013]. To overcome the problem of seeing the world as compressed in VR, some suggested that users' interactions with the environment could potentially change distance estimation in relatively short amount of time [Richardson and Waller 2005;Altenhoff et al 2012].…”
Section: Related Workmentioning
confidence: 99%
“…We often have to avoid potential obstacles and collisions by altering our whole-body trajectory and adjusting the position of the head and body segments to overcome apertures or gaps between objects. Although we easily manage to successfully perform our everyday activities, how our perception and action systems interact during learning and adaptation has been a topic of debate (Kunz, Creem-Regehr, & Thompson, 2013). In particular, wheelchair locomotion has an additional perceptual-motor requirement because the wheelchair represents an extension of the user's body that needs to be perceived and controlled (Stoffregen, Yang, Giveans, Flanagan, & Bardy, 2009).…”
Section: Introductionmentioning
confidence: 99%